Sulfur‐/Nitrogen‐Rich Albumen Derived "Self‐Doping" Graphene for Sodium‐Ion Storage. Issue 63 (9th October 2019) - Li, Siyuan; Li, Zeheng; Cao, Gaoyao; Ling, Min; Ji, Jiapeng; Zhao, Dian; Sha, Ying; Gao, Xuehui; Liang, Chengdu
Abstract: The development of sodium‐ion batteries (SIBs) is hindered by the rapid reduction in reversible capacity of carbon‐based anode materials. Outside‐in doping of carbon‐based anodes has been extensively explored. Nickel and NiS2 particles embedded in nitrogen and sulfur codoped porous graphene can significantly improve the electrochemical performance. Herein a built‐in heteroatom "self‐doping" of albumen‐derived graphene for sodium storage is reported. The built‐in sulfur and nitrogen in albumen act as the doping source during the carbonization of proteins. The sulfur‐rich proteins in albumen can also guide the doping and nucleation of nickel sulfide nanoparticles. Additionally, the porous architecture of the carbonized proteins is achieved through removable KCl/NaCl salts (medium) under high‐temperature melting conditions. During the carbonization process, nitrogen can also reduce the carbonization temperature of thermally stable carbon materials. In this work, the NS‐graphene delivered a specific capacity of 108.3 mAh g −1 after 800 cycles under a constant current density of 500 mA g −1 . In contrast, the Ni/NiS2 /NS‐graphene maintained a specific capacity of 134.4 mAh g −1 ; thus the presence of Ni/NiS2 particles improved the electrochemical performance of the whole composite. Abstract : Egged on anodes : Nitrogen‐ and sulfur‐rich doped graphene (Ni/NiS2 /NS‐graphene and NS‐graphene) composites are obtained through the built‐in heteroatom "self‐doping" of albumen in a facile molten‐salt process. These composites exhibit excellent electrical stability and reversibility (see figure).